Acquired Antibiotic Resistance Genes: An Overview - van Hoek, Angela H.; Mevius, Dik; Guerra, Beatriz; Mullany, Peter; Roberts, Adam P.; Aarts, Henk J. (Frontiers in Microbiology, 2011)
In this review an overview is given on antibiotic resistance (AR) mechanisms with special attentions to the AR genes described so far preceded by a short introduction on the discovery and mode of action of the different classes of antibiotics. As this review is only dealing with acquired resistance, attention is also paid to mobile genetic elements such as plasmids, transposons, and integrons, which are associated with AR genes, and involved in the dispersal of antimicrobial determinants between different bacteria.